Administration and cross-functional teams in libraries: A case study in failures and solutions. Issue 4 (13th June 2017) - Perrin, Joy M.; Daniel, Justin
Abstract : Purpose: The purpose of this paper is to assist library administration in avoiding cross-functional team pitfalls. Design/methodology/approach: This paper reports the results of years of cross-fucntiional teams at an academic Library. Reports results of years of cross-functional teams at an academic Library. Findings: Through shared trial and errors, readers will be able to avoid pitfalls and formulate questions not previously considered for their pursuit of cross-functional teams. Research limitations/implications: While this is a case study, the lessons learned can be applied at any library where cross-functional teams are considered. Originality/value: This study provides an account of teams at an academic library spanning a decade. Trials and tribulations are discussed.